Prevalence, co‐existence, and factors related to a change in geriatric giant syndromes over 2 years: results of the Second Wave of Cognition of Older People, Education, Recreational Activities, NutritIon, Comorbidities, fUnctional Capacity Studies (COPERNICUS) - Kujawska, Agnieszka; Kujawski, Sławomir; Zupkauskienė, Jūratė; Husejko, Jakub; Hajec, Weronika; Robertson, Claire E.; Miglis, Mitchell G.; McMahon, Nicholas; Dani, Melanie; Simões, José Augusto; Zalewski, Paweł; Kędziora‐Kornatowska, Kornelia (Psychogeriatrics, 2025)
Background We prospectively examined the prevalence, co‐existence, and change of geriatric giant syndromes in older people over 2 years. Methods Two hundred and five older subjects were examined before and after 2 years. Ten geriatric giants were assessed at both time points: cognitive impairment, depression, orthostatic hypotension, polypharmacy, sarcopenia, dynapenia, falls, chronic pain, faecal and urinary incontinence. Results Chronic pain, cognitive impairment, and urinary incontinence were three of the most commonly occurring geriatric giants at baseline (57%, 46%, and 40%). The presence of faecal incontinence, urinary incontinence, falls, depression, cognitive impairment, orthostatic hypotension, and polypharmacy was most strongly related to the number of geriatric giants in total at baseline (P < 0.05). A higher intake of dietary antioxidants by one point was related to fewer geriatric giants after 2 years (by 0.04, after adjusting for confounding factors (P = 0.03)). Conclusions Geriatric giant syndromes tend to co‐exist and change with high variability over 2 years. Higher intake of antioxidants with diet could be related to fewer geriatric giants over time.